Translational Regulation in the Mammalian Oocyte - Susor, Andrej; Kubelka, Michal (Results and problems in cell differentiation, 2017)
Fully grown oocytes arrest meiosis at prophase I and deposit maternal RNAs. A subset of maternal transcripts is stored in a dormant state in the oocyte, and the timely driven translation of specific mRNAs guides meiotic progression, the oocyte-embryo transition, and early embryo development. In the absence of transcription, the regulation of gene expression in oocytes is controlled almost exclusively at the level of transcriptome and proteome stabilization and at the level of protein synthesis.This chapter focuses on the recent findings on RNA distribution related to the temporal and spatial translational control of the meiotic cycle progression in mammalian oocytes. We discuss the most relevant mechanisms involved in the organization of the oocyte's maternal transcriptome storage and localization, and the regulation of translation, in correlation with the regulation of oocyte meiotic progression.
Keywords: maternální dědičnost; Gene Expression Regulation; transkriptom; Protein Biosynthesis; proteosyntéza; Transcriptome; meióza; Animals; Maternal Inheritance; Meiosis; Female; RNA, Messenger, Stored; ženské pohlaví; oocyty; RNA messenger skladovaná; zvířata; regulace genové exprese; Oocytes